# 2x+5-3(8+9x)=56

## Simple and best practice solution for 2x+5-3(8+9x)=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2x+5-3(8+9x)=56 equation:

`2x+5-3(8+9x)=56`

We simplify the equation to the form, which is simple to understand

2x+5-3(8+9x)=56

Reorder the terms in parentheses

2x+5+(-24-27x)=56

Remove unnecessary parentheses

+2x+5-24-27x=+56

We move all terms containing x to the left and all other terms to the right.

+2x-27x=+56-5+24

We simplify left and right side of the equation.

-25x=+75

We divide both sides of the equation by -25 to get x.

x=-3

### See similar equations:

| -(5xy-12)+4(4xy+7)= | | 14=5-2/7q | | 0.6v-0.03+0.1v=0.46 | | 5.50x+9.30(170-x)=1284.60 | | 4c=25-40.2 | | 17-5(4x+3y)= | | 5-3/8g=-8 | | (6n-1)x^5/(4n+1) | | x+2x+7=10x-7 | | -9(4f+3)=f | | (6n-1)1^5/(4n+1) | | 6=3(x+5)-4x | | 4(y+2)-6(3y+2)= | | 91-(5x+5)=5(x+4)+x | | 2(4x+6)-4(x+1)= | | 15v(v)-19v+6=0 | | 0.001x+3.1=2.03x-2.96 | | 2.7x-2.1=5.73 | | -12-3r=8 | | 105x+175-28x+196=20 | | 8(-3-4f)=f | | -7d+8+12d=-10 | | -1.3x-2.2=-2.8 | | 4.20x+5.70(4)=918.00 | | -18/5+5 | | 35(3x+5)-28(x+7)=20 | | -x^2+5x=6 | | 4.20x+5.70(4x)=918.00 | | 0.008x+0.006(x+9)=1.24+23x | | 28z-33=3 | | -2/3x-5/6=7/12 | | 1=3(x-4)+3-2x | | 2.1x+4.6(4x)=5330 | | 6(c+4)=8+5c | | 2(x+6)+3x=2(x+1)+1 | | 10w+9=3w+23 | | -2.4x-0.7=-1 | | 1/13x^2-x-26=0 | | 3x+2=2(x-7) | | 5c-8=2c-20 | | 5.40x+9.70(129-x)=941.70 | | 6(1/2) | | -6(-5-7h)=h | | -8-4x=-2x | | 6x+9=19+2x | | -9/20=x-13/16 | | 6(1/3) | | -8-4x=-2x+2 | | -3x-3=4+4x | | -7(2n+5)=n | | (2x+y)(2x+y)(2x+y)(2x+y)= | | 50=10(x-6) | | 3x-x+8=4(2x-1) | | 2y+9=6y-1 | | 4j(j)-11j+6=o | | 4-5(x+5)-7=5+2(4-2x)-16 | | 3d+2=16-1d | | 7y=17 | | 0.3b-0.05+0.4b=-0.008 | | 4.20x+5.55(155-x)=748.20 | | 9-3d=9d | | 2xy+2xy+2xy= | | 10a=17+13a | | 2.7x+4.3(2x)=2938 | | 3-9(x+1)-3=3+3(9-3x)-81 |